Dampak Modernitas dalam Novel Layar Terkembang Karya St. Takdir Alisjahbana: Perspektif Modernisme Anthony Giddens - Tri Ananda; Anshari Anshari; Suarni Syam Saguni (HUMAN: South Asian Journal of Social Studies, 2023)
Abstract.This study aims to describe the impact of modernity in the novel Layar Terkembang by St. Alisjahbana's destiny through the modernist perspective of Anthony Giddens. This study uses a qualitative type research method. The data obtained is in the form of discourse on the impact of modernity according to Anthony Giddens. Based on the results of data analysis, three impacts of modernity were found according to Anthony Giddens, namely the occurrence of damage to the physical and non-physical environment, damage to the physical environment in the form of air pollution, while non-physical, namely the fading of life values such as rebelling, not heeding the advice of older people, and atheist (does not believe in God) because modern humans think that